2020
DOI: 10.1002/chem.202002123
|View full text |Cite
|
Sign up to set email alerts
|

Highlights on the Binding of Cobalta‐Bis‐(Dicarbollide) with Glucose Units

Abstract: Metalla-bis-dicarbollides, such as the cobalta-bisdicarbollide (COSAN) anion [Co(C 2 B 9 H 11) 2 ] À ,h ave attracted much attentioni nb iology but ad eep understanding of their interactions with cell components is stillm issing. For this purpose, we studied the interactions of COSANw ith the glucosem oiety,w hich is ubiquitous at biological interfaces. Octyl-glucopyranoside surfactant (C8G1) was chosena sa model as it self-assembles in water and creates ah ydrated glucose-covered interface. At low COSAN conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…An octylglucopyranoside surfactant named C8G1 was chosen as the model because it self-assembles into the water and creates a hydrated glucose-based interface. The authors reported that COSAN strongly interacts with C8G1 to form mixed aggregates in equilibrium [66]. COSAN derivatives have shown some surfactant properties, associated with a more hydrophobic feature that provides the ability to cross biological membranes, opening up opportunities in the pharmaceutical field, including BNCT.…”
Section: Sugars and Metallacarboranesmentioning
confidence: 99%
“…An octylglucopyranoside surfactant named C8G1 was chosen as the model because it self-assembles into the water and creates a hydrated glucose-based interface. The authors reported that COSAN strongly interacts with C8G1 to form mixed aggregates in equilibrium [66]. COSAN derivatives have shown some surfactant properties, associated with a more hydrophobic feature that provides the ability to cross biological membranes, opening up opportunities in the pharmaceutical field, including BNCT.…”
Section: Sugars and Metallacarboranesmentioning
confidence: 99%
“…For this reason low charge density NIs were called "superchaotropes". [11,[14][15][16] A broad spectrum of non-ionic systems was probed regarding their binding with superchaotropic NIs, such as small aromatic molecules, [17] surfactant selfassemblies, [11,15,18,19] oligo-and polymers, [18,20,21] macrocyclic molecules [14,16,[22][23][24] and short-chain amphiphiles. [25] In a previous contribution, our group has explicitly drawn a focus on the interaction of PW with polyethylene oxide (PEO) oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…Having performed experiments in a round-bottom flask on a chemical scale, which showed that [ o -COSAN] − and some of its halogenated derivatives interact with biomolecules (carbohydrates [ 42 ], proteins [ 43 ] and DNA [ 44 ]), we have wanted to observe these interactions in vitro experiments by changing the round-bottom flask to a cell and the solutions to the physiological components of the cell. In addition, the previous studies at the chemical scale were done individually, whereas the present study incorporates the effect of all the interacting biomolecules in a cell.…”
Section: Introductionmentioning
confidence: 99%